GAMBARAN KENYAMANAN PASIEN HIV YANG MENGGUNAKAN TERAPI ANTIRETROVIRAL DI KOTA YOGYAKARTA - , PUTRY MAZAYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: In Indonesia, in 2013 the number of people living with HIV increases. There is 35.3 million people living with HIV and 1,693of them live in Yogyakarta. This condition causes disconfort in term of physical, social, psychospiritual and environment. Antiretroviral is one of the important step in tackling HIV / AIDS despite of side effects that can cause discomfort to the patients. Objective: This study is to describe the effect of antiretroviral for patientâs comfort aspect including of physical, social, psychospiritual, and environment. Method: quantitative descriptive study with cross sectional design. The sample size is as much as 56 people living with HIV on antiretroviral therapy. The data was LSM Victori taken in Yogyakarta between May-June 2014. Sampling technique was taken using Purposive Sampling method. The data were obtained using GCQ instrument (General Comfort Questionnaire) and analyzed using frequency distribution. Results: The antiretroviral regimen line 1 is the most widely used. The most common complaints experienced by respondents were nausea / vomiting, headache, and loss of appetite. Results of Physical comfort mean is 25,14 (Median= 25) , social mean is 16,55 (Median=16 psychospiritual mean is 55,94 (Median= 55,5), and environment mean is 29,66 (Median= 30).The total comfort mean 127,30 (Median=127). Thus, only environmental aspect which has mean value below the median. Conclusions: The use of antiretroviral leads to physical complaints. However, overall respondents still feel comfortable in the physical, social, and psychospiritual except for environment.